We need to talk (more wisely) about wisdom: A set of conversations about wisdom, science, and futures. (April 2019) - Ramirez, Rafael; Ravetz, Jerry; Sharpe, Bill; Varley, Leila
Highlights: Is wisdom as we know it from the past fit for the future? We doubt it. We discuss issues having to do with the nature of science and with many levels co-existing and relating to each other. We discuss issues on how the past and future meet (or fail to meet) in wisdom, and with knowledge, wisdom and complexity. We discuss how the above aspects relate to each other. We suggest ways forward: post-normal science, scenario planning, and courageous conversations. Abstract: This paper is a structured dialogue between the four authors on the question "what might constitute wisdom for the future?" With each author exploring a distinct but related angle we first consider four aspects: The traditional view of wisdom linked to philosophy and the humanities and how the development and subsequent crisis of science has eroded this; how knowledge and wisdom differ and how embracing complexity might be required to make wise decisions; how wise decisions can be contradictory across different 'levels' and how it might be possible to navigate these differences; and how wisdom involves balancing learning from the past whilst being open to the future. The second part of the paper entails reflections and comments on each of these four aspects done by two of the authors on the inputs by the other two, and vice-versa. In the third section, we share views on how wisdom is linked to action; and to decision-making and even reflection; and not just to knowledge. In assessing what constitutes wisdom for the future, our conversation suggests it is important to acknowledge and address the crises science is currently undergoing. This includes practices which embrace uncertainty, ignorance and complexity. We discuss three approaches which can be deployed, alone or together, to that effect. They are scenario planning as a tool to contemplate multiple possibilities and navigate the future; Post-Normal Science as a theory for understanding uncertainty; and hosting and supporting more meaningful and more courageous conversations.